The Role of Kerobokan Customary Village in Utilizing Land for Investment in Tourism Area Based on Local Wisdom - I Gusti Ngurah Anom; Lis Julianti; I Gusti Ayu Vina Widiadnya Putri (Universitas Pendidikan Ganesha, 2022)
This research aims explicitly to explain the authority and role of the traditional village in utilizing customary village land for investment activities for tourism areas based on local wisdom in the Kerobokan Customary Village. This study used an empirical research type, with the research subjects of the Bendesa Adat and the village Prajuru. The data collection techniques used in this study were observation, a document study, in-depth interviews, purposively selected informants, namely each of the Indigenous Prajuru in the Kerobokan Customary Village, and Focus Group Discussion. The finding showed that the Kerobokan Customary Village has a role in the use of land for investment in tourism areas. The use of customary land for tourism investment activities was carried out with a lease agreement under the supervision of the Bendesa Adat. The finding showed that the involvement of the Customary Village in maintaining the balance of Tri Hita Karana values implementing tourism investment was not optimal, which can be seen from the effect of this activity in the form of environmental pollution within the tourism area, the shifting values of the local wisdom to be more commercialism, liberalism, and individualism.